The Circular SOME Model for Instagram in RSUD Al-Ihsan's Digital Marketing Development - Aribowo, Pandith; Jusuf, Eddy; Juju, Undang (Yayasan Ilomata, 2025)
Information and communication technology disruption has greatly impacted various sectors, including the health service sector such as hospitals. As a government hospital, RSUD Al-Ihsan always tries to provide the best service, including marketing multiple services using social media to reach a wider audience. One of the right ways to develop social media is by activating social media through The Circular Model of SOME. This research uses a qualitative method with a case study approach. This research data was collected using interviews, observations, and digital documents. This research found that Al-Ihsan Regional Hospital has generally utilized the share concept by creating three pillars of content: education, information, and entertainment. The optimization concept has also been implemented by using various features on Instagram such as stories, posts, reels, and highlights. The management concept is to create fast-response content such as the Integrity Zone. Lastly, important figures such as doctors or hospital leaders should be involved to increase the trust of their Instagram followers. However, there are several shortcomings in the optimization section, such as inconsistent use of hashtags in each upload and inconsistent replies to followers' comments in the management section. Therefore, this study shows that other institutions or agencies can note the importance of content consistency and copywriting in implementing social media strategies.